Upaya Peningkatan Legalitas Usaha UMKM Desa Urang Agung Melalui Fasilitasi Penerbitan NIB - Muhammad Mufid; Muchammad Farid Fauzi; Fauzan Fauzan (STAI Nurul Islam Mojokerto, 2025)
Our KKN team applies the PAR method to carry out the Business Identification Number (NIB) creation program in Urang Agung Village. This program aims to help the community's economy by actively involving them in the NIB creation process. The implementation results show an increase in public awareness about the importance of business legality, with six entrepreneurs successfully obtaining NIB. The program also raises awareness of the benefits of NIB and highlights the importance of practical support in the administration process. The success of this program has a significant impact on the credibility of the business world and opens up new opportunities